Impact of buying attitude over consumption reduction in the context of economic crisis - Peñaloza, Verónica; Gerhard, Felipe; Monteiro, Danielli Leite Campos; Heredia, Rayén (Contextus - Revista Contemporânea de Economia e Gestão, 2018)
This study aims both to analyse the relationship of consumption reduction to the level of financial threat that people experience within contexts of economic recession and to inquire the impact of rational, compulsive, and impulsive buying attitudes on this relation. For that purpose, a study of quantitative character was carried out by applying a survey. The technique of data analysis used in this research was the moderation, by means of the Process software. The main results indicate that there is a direct relationship between the reduction of consumption and the perception of financial threat, as well as two effects on this relation: a direct moderator effect of the rational buying attitude variable and an indirect moderator effect of the compulsive buying attitude variable. However, the impulsive buying attitude variable does not show a moderator effect in the study.